2012 Proceedings IEEE INFOCOM Workshops 2012
DOI: 10.1109/infcomw.2012.6193511
|View full text |Cite
|
Sign up to set email alerts
|

Impact of traffic mix on caching performance in a content-centric network

Abstract: For a realistic traffic mix, we evaluate the hit rates attained in a two-layer cache hierarchy designed to reduce Internet bandwidth requirements. The model identifies four main types of content, web, file sharing, user generated content and video on demand, distinguished in terms of their traffic shares, their population and object sizes and their popularity distributions. Results demonstrate that caching VoD in access routers offers a highly favorable bandwidth memory tradeoff but that the other types of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
196
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(205 citation statements)
references
References 15 publications
7
196
0
2
Order By: Relevance
“…The independent reference model (IRM) has been frequently employed in literature (see [11], [12], [15] and references therein), to model how a particular object is referenced in an arbitrary traffic stream. Under the IRM model, requests for the objects/content occur in an infinite stream.…”
Section: A the Independent Reference Model (Irm)mentioning
confidence: 99%
See 1 more Smart Citation
“…The independent reference model (IRM) has been frequently employed in literature (see [11], [12], [15] and references therein), to model how a particular object is referenced in an arbitrary traffic stream. Under the IRM model, requests for the objects/content occur in an infinite stream.…”
Section: A the Independent Reference Model (Irm)mentioning
confidence: 99%
“…Empirical studies [15]- [17] have shown that the Zipf distribution renders itself as a most promising fit for describing the popularity of the content across various references. Under the Zipf popularity distribution p(i) < p(j) for i > j.…”
Section: B Content Popularity Law-a Case For Zipf Distributionmentioning
confidence: 99%
“…applying then the bounded convergence theorem (Section 13.6, [22]) to the latter identity and dividing by the expected number of requests E[λ] leads to formulas (8) and (9), as claimed.…”
Section: Irm-m Modelmentioning
confidence: 87%
“…The effect of content caching on content-centric networks where multiple applications or services are running has been investigated in [6][7][8][9]. Carofiglio et al [6,7] have clarified the role of the CS allocation method (an exclusive method) on the cache hit rate of multiple applications running on content-centric networks by means of experiments and simulations.…”
Section: Related Workmentioning
confidence: 99%
“…In the hybrid method, several VCCN router instances within a CCN router are assigned their own parts of its CS and other instances jointly use the remaining CS. Previous studies of the effects of content caching on content-centric networks have focused only on the exclusive and shared methods [6][7][8][9]. However, when content request patterns are heterogeneous, these two methods can barely maintain a balance between network fairness for VCCN slices and overall network performance.…”
Section: Introductionmentioning
confidence: 99%